2020
DOI: 10.1016/j.indmarman.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Social capital in buyer-supplier relationships: A review of antecedents, benefits, risks, and boundary conditions

Abstract: The concept of social capital advocates that the goodwill available from relations is a valuable resource that can facilitate collective actions. Although social capital has recently gained momentum in the buyer-supplier relationship (BSR) literature, there is a surprising lack of consensus about its antecedents, benefits, risks, and boundary conditions in such relationships. To address this void, a systematic literature review of seventy articles published in peer-reviewed journals between 2002 and 2018 was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 119 publications
7
71
0
Order By: Relevance
“…Partners should work hard to create their relationship; the strength of their partnership is based on their previous performance and mutual understanding (Autry & Golicic, 2010 ). Alghababsheh and Gallear ( 2020 ) establish the social capital limit in buyer–supplier relationships. Besides commercial considerations, the social aspect should also be considered in long-term buyer–supplier relationships.…”
Section: Theoretical Model and Hypotheses Developmentmentioning
confidence: 99%
“…Partners should work hard to create their relationship; the strength of their partnership is based on their previous performance and mutual understanding (Autry & Golicic, 2010 ). Alghababsheh and Gallear ( 2020 ) establish the social capital limit in buyer–supplier relationships. Besides commercial considerations, the social aspect should also be considered in long-term buyer–supplier relationships.…”
Section: Theoretical Model and Hypotheses Developmentmentioning
confidence: 99%
“…Improved logistics capabilities have also been linked to effective SCRM capabilities (Gligor and Holcomb, 2014;Wang et al, 2018;Brix-Asala et al, 2021). However, Alghababsheh and Gallear (2020) We adopted a positivist epistemological position following a deductive cross-sectional approach to test for pre-specified research hypotheses. We studied health facilities from eastern Uganda, with 122 valid responses from 52 public healthcare facilities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In a review article, Zheng (2010) found that structural and relational SC seem to reinforce each other in a feedback loop and concluded that there is no clear boundary between relational and cognitive SC, which are likely to be highly intercorrelated. In a recent review, Alghababsheh and Gallear (2020) stated that there seems to be a consensus that structural SC facilitates the development of relational and cognitive SC and that cognitive SC fosters relational SC. While the relationships among the SC dimensions are not clarified in the management literature, they are even less explored in the context of FBs.…”
Section: Future Research Agenda: the Research Gaps And Research Quest...mentioning
confidence: 99%